00.05: Validation and verification in design of structural steel connections. (13th September 2017) - Wald, František; Gödrich, Lukáš; Kurejková, Marta; Šabatka, Luboš; Kabeláč, Jaromír; Kojala, Drahoš
ABSTRACT: The only way to prove correctness of simulated results by Finite Element Analyse (FEA) is through a methodical System response quantity process. Without this approval are the results of FEA meaningless and cannot be used in design process for making any decisions. The System response quantity consist of validation, which compares the numerical solution with the experimental data, of verification, which compares computational solutions with highly accurate analytical or numerical solution, and of benchmark cases, the examples for check of the software and its user on approved and simplified input and output. In the eighties FEA of structural connection was treated by some researchers as a non‐scientific matter. Two decades later it was already a necessarily extension of experimental and analytical work. Today computational analysis, in particular computational mechanics and fluid dynamics, is commonly used as a catalyst of many research fields and an indispensable design tool. The recommendation for design by advanced modelling in structural steel is ready to be used in Chapter 5 and Annex C of EN 1993‐1‐5:2005 [1]. Development of modern general‐purpose software and decreasing cost of computational resources facilitate this trend. The FEA of structural connection is the coming step in structural steel design. As the computational tools become more readily available and easier to use even by relatively inexperienced engineers the proper procedure should be employed when judging the results of computational analysis. This paper describes the System response quantity for Component Based Finite Element Model (CBFEM) which is a multilevel FEA method to analyse and design connections of steel structures, see [2]. The steel plates in connection are analysed in CBFEM procedure by FEA. The proper behaviour of components is treated by introducing a components representing well its behaviour in term of initial stiffness, ultimate resistance and deformation capacity, of bolts, welds etc. To help with this process is prepared a contribution, which summarises the history of achievements of FEA application in structural connections. Contribution shows the currents trends in advanced modelling of connection components and differences of the research oriented design oriented models. The particular attention is dedicated to design models of generally loaded endplates.